MINISTRY of GENEROSITY - A proposal for the Democratization of Prosperity fostering the CULTURE of GENEROSITY - Vicente Pironti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This thesis examines the critical role of education in societal transformation, drawing on Werner Jaeger's assertion that the state is the primary agent of education and cultural evolution. In